CONTRIBUTION OF JOB STRESS IN MEDIATING ASPECTS AFFECTING WORK FATIGUE OF MINISTRY OF RELIGIOUS AFFAIRS EMPLOYEES IN THE SOUTH PAPUA PROVINCE REGION - Risanti, Dwi; Ratang, Westim; Wibowo, Martino (Transpublika Publisher, 2024)
Employees working for the Ministry of Religion in the South Papua Province have a range of tasks related to community service in religious affairs. The demanding workload in this role calls for extra effort from the employees. This research aims to explore how work stress acts as a mediator in the relationship between leadership style, workload, and income adequacy with work fatigue among Ministry of Religion employees in the South Papua Province. Data was collected through a survey involving 153 participants. The findings from the structural equation modeling analysis reveal that leadership style has a significant negative impact on work stress, while workload has a significant positive impact on work stress. However, income adequacy does not seem to affect work stress. Moreover, leadership style negatively impacts work fatigue, whereas workload has a positive impact on work fatigue. Income adequacy, on the other hand, does not have a significant impact on work fatigue. The study ultimately concludes that work stress plays a role in mediating the relationship between leadership style and workload with work fatigue. However, work stress does not mediate the effect of income adequacy on job burnout.